KUALITAS PELAYANAN IZIN MENDIRIKAN BANGUNAN (IMB) RUMAH TINGGAL DI KECAMATAN KRAMAT JATI JAKARTA TIMUR - Sudrajat, Della Arumnitas; Munjin, R. Akhmad; Purnamasari, Irma (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2015)
This study aims to determine how service quality of Building Permit in District Kramat JatiResidential, East Jakarta. The population in this research is 48 people in the district who filed a Keramat Jati Residential petition. The method used in this research is descriptive analysis. The sampling technique used in this study is Incidental Sampling, which sampling technique by coincidence, that anyone who by chance met with the researchers can be used as a sample, which is deemed suitable by research. Then the amount used as many as 48 people. Theory framework used in this study is Ratminto and Winarsih 2006. Service is an activity or a description of the activities that take place in the direct interaction between a person with another person or machine physically and provide customer satisfaction. The result is that the services provided by the Kramat Jatiâs subdistrict officer for the community applicant Building Permit Residential, located in the Good criteria with interpretation number is 3.52. The conclusion of this study is still a lack of discipline of officers in the service process that makes the event of delay that hinder the implementation of the applicant service Building Permit Residential, the researchers recommend the discipline of officers need to be improved so that every service process can run well and can improve quality of care provided to the public.Keywords : Quality Service, Building Permit, the Applicant Building Permit